BAKTI SOSIAL PEMBERSIHAN LINGKUNGAN MASJID JAMI’ AT-TAQWA ONEKORE DALAM RANGKA PANCA WINDU UNIVERSITAS FLORES KE-40 TAHUN 2020 - Fatma Wati; Ariswan Usman Aje; Marsel Nande; Elias Beda (LPPM Universitas Flores, 2020)
The implementation of this community service activity is motivated by a global issue that is currently developing, namely the spread of the COVID 19 virus. The spread of the virus, which also occurs in Ende district, has awakened various parties to implement a clean lifestyle, make efforts to prevent and break the chain of spread of the COVID 19 virus. One of these efforts is realized through this community service activity, namely by cleaning, socializing and spraying disinfectants in public areas. One of the areas that became the target of this dedication was the Jami At'Taqwa Onekore Ende Mosque. To achieve the goal of this Community Service activity is carried out through several approaches, including; 1) Participatory Rural Appraisal (PRA) Model which emphasizes community involvement in all activities starting from planning, implementing and evaluating activity programs, 2) Participatory Technological Development Model which utilizes appropriate technology based on local knowledge and wisdom, 3) Model Community development is an approach that involves the community directly as the subject and object of implementation of community service activities, 4) Persuasive, namely an approach that is appeal and support without coercion for the community to take an active role in this activity, 5) Educative, namely the socialization, training and mentoring as a means of transferring knowledge and education. The results of the Social Service Activities for cleaning the environment of the Jami 'At-Taqwa Onekore Mosque can run well in accordance with the activity plan, namely cleaning the mosque environment, cleaning irrigation ditches, transporting garbage and spraying disinfectants. This is shown from the following conclusions; 1) All residents become enthusiastic training participants and have a good commitment to all the programs discussed before the activity for the sake of creating a sense of security and peace in worship in the midst of the Covid 19 pandemic, 2) There has been an increased understanding of the knowledge of the Covid 19 outbreak and how to maintain security self in minimizing outbreaks. Namely by means of 3M (Keeping Distance, Washing Hands and Wearing Masks), 3) A place of worship that is clean, safe and comfortable and has a safe distance limit mark in worship.